A method for authentication of multi-user key management using quantum key distribution over noiseless channel - Buhari, Abudhahir (2015)
Quantum Cryptography (QC) is the emerging field of the current world and the potential player of the future. Quantum Key Distribution (QKD) is the matured discipline of QC and available in the market to establish a secret key between parties. In order to achieve in multiparty, basically quantum entanglement has been applied over a theoretical settings. However, due to practical limitation, entanglement based research has a feasible difficulty with current technology. The thesis principal goal is to propose a framework for quantum protocol layer for secure key management without entanglement over multiparty environment. In the secret key management, conference key or Multiparty QKD (MQKD) and joint-venture key or Public Shared Secret Quantum Key (PSSQK) protocols acted as a top layer and quantum user authentication scheme as a middle layer and the standard QKD operation as a bottom layer. The proposed secrete key management protocols are based on secret key between parties using QKD, modified error correction code and linear independent matrix. These protocols require only classical communication and yield higher secret key rate regardless of distance and noise. The security analysis using guessing entropy has applied and results shows only negligible amount information can be extracted during eavesdropping. The challenge-challenge response technique has been applied to proposed quantum user authentication scheme for verification of quantum user. This is a bidirectional authentication scheme and requires both quantum and classical channel to execute and has two modes of operation, i.e., initial and session authentication.Due to deterministic key distribution orientation, the efficiency of protocol reaches up to 100% in terms of reduction of photon wastage during communication. Further, this scheme is resilient to various quantum security attacks However, this scheme requires noiseless quantum channel in order to detect the insider and outsider attacks during authentication. A GUI based discrete event simulation has developed using OptiSystem™ in order to test the practical feasibility of proposed quantum cryptography protocol layer. The polarized based discrete variable QKD protocols have been designed and analyzed. Due to lack of real receiver setup, the results have showed lower quantum bit error rate. Further, we analyzed the impact of polarization structure of qubit due to noise, loss and distance over fiber optics and free space. A multiparty QKD setuphas been designed based on frequency division multiplexing (FDM) centralized quantum channel server. This approach reduces the requirement of total quantum channel from N*(N-1)/2 to N and each party requires one quantum channel to communicate with all other parties. The bit commitment protocol and message authentication in the layer has considered for the future research direction.